2005
DOI: 10.1158/1078-0432.ccr-04-2551
|View full text |Cite
|
Sign up to set email alerts
|

Increased Expression and Activity of CDC25C Phosphatase and an Alternatively Spliced Variant in Prostate Cancer

Abstract: Alterations in the control of cell cycle progression have been implicated in a wide variety of malignant neoplasms, including prostate cancer. CDC25 phosphatases belong to the tyrosine phosphatase family and play a critical role in regulating cell cycle progression by dephosphorylating cyclin-dependent kinases at inhibitory residues. CDC25C plays an important role in the G 2 -M transition by activating Cdc2/Cyclin B1 complexes. To determine whether CDC25C activity is altered in prostate cancer, we have examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 28 publications
3
48
0
Order By: Relevance
“…Several groups have shown previously that expression of CDK1 is increased in human PCa relative to normal prostatic tissues (Mashal et al, 1996;Kallakury et al, 1997Kallakury et al, , 1998. Cdc25C, an upstream activator of CDK1, is found not only upregulated in PCa but is also present exclusively in its active form (Ozen and Ittmann, 2005). Cdc25B, another activator of CDK1, is overexpressed in PCa.…”
Section: Discussionmentioning
confidence: 97%
“…Several groups have shown previously that expression of CDK1 is increased in human PCa relative to normal prostatic tissues (Mashal et al, 1996;Kallakury et al, 1997Kallakury et al, , 1998. Cdc25C, an upstream activator of CDK1, is found not only upregulated in PCa but is also present exclusively in its active form (Ozen and Ittmann, 2005). Cdc25B, another activator of CDK1, is overexpressed in PCa.…”
Section: Discussionmentioning
confidence: 97%
“…Interestingly, we have found that the most highly overexpressed cell-cycle-regulatory genes in androgen-independent PCa are Cdk1, cyclin B1, and cyclin B2 (3.3, 2.7, and 2.6-fold increases in median expression, respectively), with the cyclin B1 increase being statistically significant (6). Previous studies have also found increased expression of cyclin B1 and Cdc25 in PCa, and this has been associated with more aggressive PCa and progression to androgen-independent PCa (39)(40)(41). Based on these observations, we examined androgen-independent PCa cells to determine whether Cdk1 may mediate enhanced responses to low levels of androgen.…”
Section: Roscovitine Abrogates Ar Stabilization At Low Androgen Levelmentioning
confidence: 95%
“…Splicing isoforms can also arise from noncancer cells in the tumor stroma, including endothelial, mesenchymal, and immune components. In human solid tumors of the colon and prostate, alternatively spliced Cdc25s variants correlated with agressive disease, recurrence and differentiation (Hernandez et al, 2001;Ozen and Ittmann, 2005). Molecular identification and functional …”
Section: Tff1 Transforming Functions and Cdc25 Phosphatases S Rodrigumentioning
confidence: 99%